2013
DOI: 10.1002/ejic.201201404
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Spectroscopic Studies of Propylphosphonic Acid Functionalized SBA‐15 Mesoporous Silica: Characterization of Hydrogen‐Bonding Interactions

Abstract: This work aims to investigate the local structure of mesoporous silica of the type SBA‐15 functionalized with propylphosphonic acid groups by means of an extensive solid‐state NMR spectroscopic study. Here, the functionalized SBA‐15 samples are obtained by a one‐step synthetic method that allowed us better control over the loading and the distribution of the surface functions. In addition to NMR spectroscopy, the materials are characterized by X‐ray diffraction, nitrogen adsorption–desorption and transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…to phosphonic groups interacting through hydrogen-bonding with residual water, which resulted to be present in this sample in larger amount with respect to PSSA / NTMPA and can determine a shielding effect on phosphorous nuclei [33]. Moreover, unlike the resonance at 13 ppm, no spinning sidebands were observed for such lower-chemical-shift signals, suggesting that, as expected, water can determine an increased mobility of phosphonic groups [41].…”
Section: Thermal Behaviormentioning
confidence: 65%
See 1 more Smart Citation
“…to phosphonic groups interacting through hydrogen-bonding with residual water, which resulted to be present in this sample in larger amount with respect to PSSA / NTMPA and can determine a shielding effect on phosphorous nuclei [33]. Moreover, unlike the resonance at 13 ppm, no spinning sidebands were observed for such lower-chemical-shift signals, suggesting that, as expected, water can determine an increased mobility of phosphonic groups [41].…”
Section: Thermal Behaviormentioning
confidence: 65%
“…Moreover 31 P solid-state NMR, and in particular 31 P isotropic chemical shift, has been exploited for obtaining structural information on possible complexes between NTMPA and tin [34], calcium [35,36] and zirconium-titanate [37] in several organic-inorganic hybrid systems. To the best of our knowledge NMR studies on condensation of NTMPA P-OH groups have not been reported yet, while this and other structural and dynamic properties have been investigated in several works, mainly based on 31 P and 1 H solid-state NMR experiments, on polymeric organic phosphonic acids for applications in proton exchange membranes fuel cells [10,11,38,39], layered microporous tin biphosphonates [40] and mesoporous silica functionalized with phosphonic acids [41]. to phosphonic groups interacting through hydrogen-bonding with residual water, which resulted to be present in this sample in larger amount with respect to PSSA / NTMPA and can determine a shielding effect on phosphorous nuclei [33].…”
Section: Thermal Behaviormentioning
confidence: 99%
“…[12][13][14][38][39][40][41] The disappearance of ethyl group (-C 2 H 5 ) in PO(O-C 2 H 5 ) and Si-OC 2 H 5 is due to the concentrated HCl treatment. 31 P single pulse NMR spectra were also recorded for the DPTS, DP20*, and DP20*-OH samples (see 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 NMR pattern similar to that of DP20*.…”
Section: Ppm Peak Can Be Masked By That Corresponding To Methylene Camentioning
confidence: 98%
“…phosphorous environments, surface interactions between phosphrous in phosphonic acid and the framework. The peaks at δ=33 and 23 ppm can be assigned to hydrogen bond acceptor and donor, respectively [12][13][14][38][39][40][41]. According to the literature, phosphonic acid group acts as a hydrogen bond donor via P-OH groups and hydrogen bond accepter via the P=O bond.…”
mentioning
confidence: 99%
“…These -NH and -OH hydrogens are mobile due to the formation of hydrogen-bonding network between MTet groups and phosphonic acid units of VPA, so we cannot only determine the structure with 1 H NMR spectra. Previously, especially solid-state NMR spectroscopy was studied and reported to elucidate the structure and the local proton diffusion of the PVPA homopolymers [41][42][43][44][45][46][47] and copolymers. [ 38,43,45 ] Copolymerization of VPA with MTet generates new resonances.…”
Section: Samplementioning
confidence: 99%